(untitled) (Bangladesh Pharmaceutical Journal, 2019)
Hemigraphis hirta has been used by folk practitioners to alleviate symptoms of several diseases, although the pharmacological activities of this plant have not been thoroughly explored. The current study was designed to assess the anti-diarrheal and CNS depressant activities of H. hirta in mice model. For both assays, the experimental mice received the methanolic crude extract and its petroleum ether soluble fraction at dose of 200 and 400 mg/kg body weight which are denoted as CME 200, CME 400, PESF 200 and PESF 400, respectively. Both fractions remarkably attenuated castor oil-induced diarrheal effect in a dose-dependent manner and the results were comparable to standard loperamide (89.47%). Among all, PESF 400 exhibited statistically significant (p < 0.01) anti-diarrheal activity as demonstrated by 78.95% inhibition of defacetion. Compared to reference drug diazepam, all the tested samples considerably shortened the time for onset of sleep and prolonged the duration of phenobarbitoneinduced sleep in mice. The results of our present study, being reported for the first time, demonstrate that the methanol extract of leaves of H. hirta and its organic soluble partionates possesses significant anti-diarrheal and CNS depressant properties. However, this preliminary screening requires further detailed investigation to confirm these findings as well as to isolate and characterize the bioactive compounds. Bangladesh Pharmaceutical Journal 22(2): 176-180, 2019